Argument Coreference Between Content Verbs and Predicative Nouns in Brazilian Portuguese: A Pilot Corpus Study (Revista de Estudos da Linguagem, 2024)
The literature on complement clauses and support/light verb constructions provides most of the available information on coreference between arguments of matrix and subordinate syntactic predicates. However, this phenomenon is largely unexplored when it comes to verb phrases consisting of a content verb and a predicative noun in object position, such as declarar paixão (“declare passion”), cumprir a promessa (“fulfill the promise”), responder perguntas (“answer questions”), or resistir à tentação (“resist temptation”). The notions of obligatory and non-obligatory coreference do not fully explain this phenomenon, since non-coreferential usage of these phrases leads to different types of coercion, which are relevant properties to classify these phrases. This paper proposes a pilot study of verb phrases of this kind, extracting them from a Brazilian Portuguese newspaper corpus aiming at their syntactic-semantic classification. This procedure revealed a total of 75 such verb phrases. Based on semantic coercion and distributional properties, four major classes divided into seven subclasses are proposed to cover two-thirds of the data. There is also a fifth class with 17 items in which coreference appears to be a contextual property, i.e., unrelated to lexical semantics, and eight hapax legomena. The results provide a new perspective on this understudied topic, identifying also irregular aspects deserving further studies